Implementasi Kebijakan Peraturan Daerah Kawasan Tanpa Rokok Dan Terbatas Merokok Kota Probolinggo - Arini Dwi Megayanti; Mohammad Natsir (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2024)
In an effort to protect the human rights of every human being to be able to breathe fresh and clean air or be free from cigarette smoke, as well as in an effort to improve the health of the people of Probolinggo City while still respecting the rights of smokers, the Probolinggo City Government has issued Probolinggo City Regional Regulation (Perda) No. . .12 of 2012 concerning No-Smoking and Limited Smoking Areas and Probolinggo Mayor (Perwali) Regulation No. 118 of 2021 concerning Implementation Guidelines for Probolinggo City Regional Regulation no. 12 of 2012 concerning No-Smoking and Limited Smoking Areas. After this regulation has been in effect for 11 years, it turns out that there are still many violations of non-smoking areas and restricted smoking areas. This research aims to determine the implementation of Regional Regulations regarding No-Smoking and Limited-Smoking Areas in Probolinggo City and identify obstacles in implementing these Regional Regulations. The research method used in this research is a qualitative descriptive method. Interviews and observations were carried out in the No-Smoking Area (SMA Negeri 1 Probolinggo) and the Limited-Smoking Area (Mayangan Subdistrict, Mayangan District, Probolinggo City). The informants in this research were the Probolinggo City Health Service and the Probolinggo City Civil Service Police Unit.The results of the research show that the implementation of regional regulations in non-smoking areas has gone well, while in restricted smoking areas it has not gone well.